Functional patterns of cytomegalovirus (CMV) pp65 and immediate early‐1‐specific CD8+ T cells that are associated with protection from and control of CMV DNAemia after allogeneic stem cell transplantation. Issue 3 (1st June 2015) - Giménez, E.; Muñoz‐Cobo, B.; Solano, C.; Amat, P.; de la Cámara, R.; Nieto, J.; López, J.; Remigia, M.J.; Garcia‐Noblejas, A.; Navarro, D.
Abstract Background The functional profile of cytomegalovirus (CMV)‐specific CD8+ T cells that associate with protection from and control of CMV DNAemia in allogeneic stem cell transplant (allo‐SCT) recipients remains incompletely characterized. Methods We enumerated pp65 and immediate early (IE)‐1‐specific CD8+ T cells expressing interferon‐gamma, tumor necrosis factor‐alpha, and CD107a, by flow cytometry in 94 patients at days +30 and +60 after allo‐SCT. Results Fifty of 94 patients had CMV DNAemia within the first 100 days after transplant. CMV‐specific CD8+ T‐cell responses (of any functional type) were more likely to be detected in patients who did not display CMV DNAemia than in those who did (P = 0.04). Qualitatively, no major differences in the functional signature of CMV‐specific CD8+ T cells were noted between patients who had or did not have CMV DNAemia. Patients displaying levels of polyfunctional CD8+ T cells at day +30 >0.30 cell/μL had a lower risk of CMV DNAemia (positive predictive value 76%, and negative predictive value 43%). Conclusion The presence of polyfunctional CD8+ T cells (either expressing CD107a or not) was associated with lower levels of CMV replication, and higher frequency of self‐resolved episodes. The data reported further clarify the role of polyfunctional CD8+ T cells in control of CMV DNAemia in allo‐SCT recipients.